Pengaruh Komunikasi Sosial Antar Budaya Terhadap Etika Karyawan Di Perseroan Terbatas Surya Madistrindo - Nyoman Rycko Dwicahya Ary Sanjaya (PT. Gauri Narendra Patraka, 2023)
Employee ethics at work have an influence on company performance because it is a system that supports the achievement of company targets and goals. Social communication and intercultural communication are some of the determining factors for employees in forming a work atmosphere that supports employee performance productivity, so researchers are interested in conducting research related to